17 de Marzo (Santa Cruz, Argentina): A new distal source of Pampa del Asador type black obsidian and its implications for understanding hunter-gatherer behavior in Patagonia - Franco, Nora Viviana (2017)
Most obsidian artifacts from central and southern Patagonia were made of black obsidian from Pampa del Asador (PDA), an extended secondary source area centered at approximately 47°55′S and 71°08′W. Artifacts of obsidian from PDA have been found <600 km to both the northeast and south and along the Atlantic coast 300 km to the east of this major source area. Here we report a newly -discovered distal source of PDA- type black obsidian pebbles at 17 de Marzo (17M) located ~170 km southeast of the main PDA source area. ICP-MS trace element data confirm that the relatively small (≤48 mm) black obsidian pebbles from 17M are chemically similar to the four different types of PDA black obsidian. The dimensions of the pebbles compared to the sizes of PDA obsidian artifacts from archaeological sites in the vicinity of 17M, which date from as early as the late Pleistocene-Holocene transition, indicate that early hunter-gatherers could have used the pebbles from this distal secondary source of PDA obsidian to make tools. The pebbles appear to have been transported by fluvial-glacial processes along an ancient Chico River valley to their present site. 17M is part of the "Patagonian Gravel" deposits, which are widespread along the present Chico River valley suggesting that other distal PDA obsidian pebble sites along the river valley may possibly await discovery. The potential widespread availability of PDA obsidian pebbles along the Chico River drainage valley may help to explain why so many artifacts in this area were made of black PDA obsidian. Results obtained indicate that we can no longer assume that hunter-gatherers obtained raw PDA-type black obsidian only from PDA specific source. Black obsidian may have also been available, perhaps in pockets, over a considerable area east and up to ~170 km distant southeast of PDA.